2015
DOI: 10.1186/s13395-015-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

Akt-mediated phosphorylation controls the activity of the Y-box protein MSY3 in skeletal muscle

Abstract: Background: The Y-box protein MSY3/Csda represses myogenin transcription in skeletal muscle by binding a highly conserved cis-acting DNA element located just upstream of the myogenin minimal promoter (myogHCE). It is not known how this MSY3 activity is controlled in skeletal muscle. In this study, we provide multiple lines of evidence showing that the post-translational phosphorylation of MSY3 by Akt kinase modulates the MSY3 repression of myogenin. Methods: Skeletal muscle and myogenic C2C12 cells were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…On the other hand, it was also reported that acute stimulation of YB-1 phosphorylation does not promote YB-1 nuclear translocation ( 25 ) and both phosphorylated and non-phosphorylated YB-1 can be detected in the nucleus ( 53 ). Contrary to the reports that phosphorylation of YB-1 promotes its binding to DNA, the study on mouse MSY3 (YB-3) showed that phosphorylation decreases its binding to DNA ( 54 ). MYS3 is a close family member of YB-1.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, it was also reported that acute stimulation of YB-1 phosphorylation does not promote YB-1 nuclear translocation ( 25 ) and both phosphorylated and non-phosphorylated YB-1 can be detected in the nucleus ( 53 ). Contrary to the reports that phosphorylation of YB-1 promotes its binding to DNA, the study on mouse MSY3 (YB-3) showed that phosphorylation decreases its binding to DNA ( 54 ). MYS3 is a close family member of YB-1.…”
Section: Discussionmentioning
confidence: 64%
“…Upon denervation, AChRs are destabilized and their synthesis increases, resulting in a strong increase in their turnover rates 1622 . In non-synaptic muscle regions, release of the repression of synaptic genes promotes ectopic AChR cluster formation 2326 . HDAC4 induction and HDAC9 repression control the underlying epigenetic and transcriptional changes following denervation 2628 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the differences in AKT between treatments, we hypothesize that lower phosphorylation of AKT in LOW facilitated lower myogenic regulatory factor expression compared to AD. AKT is an important upstream regulator of myogenesis [28,29]. Overexpression of AKT in C2C12 myoblasts induces myogenic differentiation by increasing myogenic regulator factor expression to simulate myotube formation, while inhibition of AKT decreases myogenesis [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…AKT is an important upstream regulator of myogenesis [ 28 , 29 ]. Overexpression of AKT in C2C12 myoblasts induces myogenic differentiation by increasing myogenic regulator factor expression to simulate myotube formation, while inhibition of AKT decreases myogenesis [ 28 30 ]. In the current study, alterations in myogenesis via AKT were likely through downstream activation of GSK-3β [ 31 ].…”
Section: Discussionmentioning
confidence: 99%